1960
DOI: 10.2105/ajph.50.3_pt_1.338
|View full text |Cite
|
Sign up to set email alerts
|

Potentialities and Limitations of Medical Data on Official Birth Certificates

Abstract: TO KEEP ABREAST of changes in the characteristics of a population with regard to pregnancies and newborns and to keep public health programs in this area geared to these changes, it is desirable and helpful to collect and study comprehensive statistics with which to measure and evaluate these changes and the program needs which they entail. A simple and inexpensive method of collecting source data for such statistics is through the addition of a medical supplement to the birth certificate. Yet, this method has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1962
1962
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, with the use of live birth certificate information many difficulties arise which should be resolved in order for the resultant data to be meaningful. Foremost is the problem of incompleteness of reporting, a matter commented on by a number of our respondents and discussed by many experts (5)(6)(7)(8)(9)(10)). This incompleteness is due to a number of factors, among which are the following.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the use of live birth certificate information many difficulties arise which should be resolved in order for the resultant data to be meaningful. Foremost is the problem of incompleteness of reporting, a matter commented on by a number of our respondents and discussed by many experts (5)(6)(7)(8)(9)(10)). This incompleteness is due to a number of factors, among which are the following.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…5. The questions asked should be periodically reviewed, so that obsolete items may be deleted and new ones added as medical progress is achieved. 6. The questions should be carefully worded to avoid ambiguity.…”
Section: Lack Of Awareness Of the Value Of Accuratementioning
confidence: 99%
“…This study was reported in part at the 116th annual meeting of the American Public Health Association, Boston, MA, November [13][14][15][16][17] 1988.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Anomalies of the distribution of gestational age obtained by clinical estimate included obvious digit preference (higher frequencies with even weeks) and as many as 87% of values concentrated in the single week's category for 40 weeks, a finding considered unrealistic. [9][10][11] However, the limitations of LMP-based gestational age determinations have also been reported widely in the scientific literature. Several factors may lead to an error in gestational age derived from the LMP, including irregularities of menstrual cycle, individual variation in length of the cycle, preconception amenorrhea following oral contraceptives, implantation bleeding or other bleeding early in pregnancy, and recall errors by mothers.…”
Section: Introductionmentioning
confidence: 99%